2011
DOI: 10.17221/249/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, lead, and mercury concentrations in tissues of roe deer (Capreolus capreolus L.) and wild boar (Sus scrofa L.) from Lowland Croatia

Abstract: Srebočan E., Prevendar Crnić A., Ekert-Kabalin A.M., Lazarus M., Jurasović J., Tomljanović K., Andreić D.,. Strunjak Perović I., Čož-Rakovac R. (2011): Cadmium, lead, and mercury concentrations in tissues of roe deer (Capreolus capreolus L.) and wild boar (Sus scrofa L.) from Lowland Croatia. Czech J. Food Sci., 29: 624-633.Cadmium, lead, and mercury concentrations were determined in roe deer and wild boar tissues (muscle, liver, kidney) of three different age groups from lowland Croatia. Cadmium concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…Results are in line with previously published Hg levels in brown bears from Croatia [29] and Slovakia, [20,21] but higher than those in red deer [32] and roe deer [38] from Croatia. However, Srebo can et al [38] found Hg levels in wild boar muscle above that of the brown bears studied here. The same animals had comparable Hg in liver, and even lower levels in kidney, than bears.…”
Section: Mercurysupporting
confidence: 92%
See 1 more Smart Citation
“…Results are in line with previously published Hg levels in brown bears from Croatia [29] and Slovakia, [20,21] but higher than those in red deer [32] and roe deer [38] from Croatia. However, Srebo can et al [38] found Hg levels in wild boar muscle above that of the brown bears studied here. The same animals had comparable Hg in liver, and even lower levels in kidney, than bears.…”
Section: Mercurysupporting
confidence: 92%
“…The available literature also reveals that the Croatian brown bear had the highest mean renal concentration of Cd, [18,20,21] but the authors of these reports failed to specify whether the entire kidney or kidney cortex was sampled, so this comparison is uncertain. The brown bears from this study had more Cd compared to other wildlife from Croatia: red deer, [32] roe deer, wild boar, [38,39] and grey wolf. [33] The reasons for this are not apparent.…”
Section: Seleniummentioning
confidence: 74%
“…Identification of heavy metal concentrations in the organs of free-living animals provides an indirect measure of environmental pollution while making it possible to determine the extent of exposure of animals to these elements in a given area. Roe and red deer are among the common even-toed species of game animals used for bioindication/biomonitoring of environmental pollution in land ecosystems [14,15]. Their bioindicative value results mainly from wide geographic distribution, relatively small home range, territorial living and browsing nutrition strategy, relatively long life-span, huge availability of basic data and relatively simple sampling procedure [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Weekly exposure to Cd, Pb, and Hg from meat and liver was estimated based on mean or 95 th percentile metal levels [34][35][36][37]. Wild boar was hunted at locations 9,10,11,12,13,14,15,16,17,18,19 (based on references [33][34][35][36][37][38]. Pheasant and hare were hunted at hunting estate Molve -1 (based on references 29,30) and three consumption scenarios, i.e.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…However, the vast majority of game is not controlled for residues because non-marketed food is not subject to these tests. Data about toxic metal levels in free-living game from Croatia are mainly limited to scientific research (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In 2012, the Croatian Food Agency published a heavy metal exposure assessment (40) based on data for wild boar meat, liver, and kidney.…”
mentioning
confidence: 99%